2016
DOI: 10.1080/10428194.2016.1201567
|View full text |Cite
|
Sign up to set email alerts
|

Anti-tumor efficacy study of the Bruton’s tyrosine kinase (BTK) inhibitor, ONO/GS-4059, in combination with the glycoengineered type II anti-CD20 monoclonal antibody obinutuzumab (GA101) demonstrates superiorin vivoefficacy compared to ONO/GS-4059 in combination with rituximab

Abstract: The activated B-cell diffuse large B-cell-like lymphoma (ABC-DLBCL) correlates with poor prognosis. The B-cell receptor signaling pathway is known to be dysregulated in NHL/CLL and given BTK is a downstream mediator of BCR signaling, BTK constitutes an interesting and obvious therapeutic target. Given the high potency and selectivity of the BTK inhibitor, ONO/GS-4059, it was hypothesized that, the anti-tumor activity of ONO/GS-4059 could be further enhanced by combining it with the anti-CD20 Abs, rituximab (RT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 30 publications
2
5
0
Order By: Relevance
“…While the impairment of the ADCC of anti-CD20 mAbs by ibrutinib may be partly due to decreased CD20 expression on the surface of CLL cells [ 23 ], we observed that the enhanced ADCC of Fc- and glycoengineered obinutuzumab was less disturbed by ibrutinib than that of rituximab, similar to ADCC-induced cell lysis as well as NK cell activation and degranulation as surrogate markers in autologous systems [ 24 ]. Also with the second-generation of irreversible BTK inhibitors, the ADCC of obinutuzumab against CLL cells was less impaired than that of rituximab, in agreement with reports about the interference of acalabrutinib or tirabrutinib with the ADCC of anti-CD20 mAbs against Mec1 or SUDHL-4 cells, respectively [ 25 ]. The different capacity of ibrutinib and acalabrutinib for interfering with the ADCC of anti-CD20 mAbs became apparent, at inhibitor concentrations of 1 μ M ( Figure 5(a) ) or 10 μ M [ 26 ] in combinations with rituximab or obinutuzumab, respectively.…”
Section: Discussionsupporting
confidence: 88%
“…While the impairment of the ADCC of anti-CD20 mAbs by ibrutinib may be partly due to decreased CD20 expression on the surface of CLL cells [ 23 ], we observed that the enhanced ADCC of Fc- and glycoengineered obinutuzumab was less disturbed by ibrutinib than that of rituximab, similar to ADCC-induced cell lysis as well as NK cell activation and degranulation as surrogate markers in autologous systems [ 24 ]. Also with the second-generation of irreversible BTK inhibitors, the ADCC of obinutuzumab against CLL cells was less impaired than that of rituximab, in agreement with reports about the interference of acalabrutinib or tirabrutinib with the ADCC of anti-CD20 mAbs against Mec1 or SUDHL-4 cells, respectively [ 25 ]. The different capacity of ibrutinib and acalabrutinib for interfering with the ADCC of anti-CD20 mAbs became apparent, at inhibitor concentrations of 1 μ M ( Figure 5(a) ) or 10 μ M [ 26 ] in combinations with rituximab or obinutuzumab, respectively.…”
Section: Discussionsupporting
confidence: 88%
“…Constitutive activation of STAT6 pathway in PMBL has been previously reported by other investigators [27]. Differential regulation of AKT phosphorylation by obinutuzumab has also been reported in a 3D NHL model [28,29]. STAT6, NF-κB and PI3K/AKT pathways were reported to be activated in PMBL [2,23].…”
Section: Discussionsupporting
confidence: 65%
“…Tirabrutinib is a covalent type inhibitor with comparable efficacy to ibrutinib in the treatment of B-cell malignancies (Walter et al, 2016) and has greater selectivity for Btk ( in vitro IC 50 , 2 nmol/L) and Tec ( in vitro IC 50 , 5 nmol/L) than other kinases, including Lck, Fyn, Lyn and Itk (KINOMEscan platform: 442 kinases) (Yasuhiro et al, 2017). Tirabrutinib inhibits cell proliferation in some malignant B-cell lines but does not inhibit the activation of T-lymphocytes from human PBMCs (Kozaki et al, 2018).…”
Section: Introductionmentioning
confidence: 99%